Automating Server Deployment With Ansible to Improve Performance, Virtualization, and Network Security - Abdhul Nur Hidayat; Andi WRE (Green Publisher Indonesia, 2025)
Modern IT infrastructure management faces challenges in automation, virtualization, and network security. Manual processes in server management often lead to inefficiencies and potential misconfigurations. This research aims to develop a method of automating server deployment using Ansible, integrating container-based virtualization, and implementing network security policies with FortiGate. Methods used include the implementation of Ansible automation scripts, testing virtual environments using Docker, and configuring FortiGate firewalls to improve network security. The results show that automation with Ansible speeds up the deployment process, improves the efficiency of server resource management, and strengthens network security with more consistent and scalable firewall configurations. The integration of this technology provides an efficient, flexible, and secure solution to modern IT infrastructure.